A focused review of carbon corrosion mechanism in proton exchange membrane fuel cell during start-up and shut-down processes. Issue 2 (1st June 2023) - Mansir, Ibrahim B.; Okonkwo, Paul C.
ABSTRACT: Degradation and poor performance in proton exchange membrane fuel cells can be traced back to corrosion of the carbon produced by electrochemical activities at the catalyst layers. With greater potential, such as those present during startup and shutdown, carbon corrosion can be more severe. Understanding the carbon degradation mechanism when subjected to the anhydrous and electrochemical conditions in the fuel cell is highly critical, especially at the start-up and shut-down successions. Insight into carbon corrosion in proton exchange membrane fuel cell settings is provided by this review. In this article, we discuss how hydrogen and oxygen can affect carbon corrosion, and how microscopic inspection can be used to determine the corrosion mechanism. Through this systematic review, the risk of oxidation of the carbon support at high cathode voltage can be mitigated by employing good system methods for start-up and shut-down involving catalyst-support technology. Furthermore, utilizing a high flow rate of hydrogen during start-up and a high flow rate of air cleansing of the anode during shut-down can diminish carbon corrosion. Carbon corrosion can be reduced, and fuel cell performance enhanced by following the advice provided in this evaluation and making use of more stable carbon support material and cost-effective system processes.